MicroRNA-497-5p negatively regulates the proliferation and cisplatin resistance of non-small cell lung cancer cells by targeting YAP1 and TEAD1 - Zeng, Shang-Gan; Xie, Jian-Hong; Zeng, Qun-Ying; Dai, Shao-Hua; Wang, Yun; Wan, Xue-Mei; Zhou, Xue-Liang (Translational Cancer Research, 2019)
Background: MicroRNAs (miRNAs) are crucial regulators in the pathological processes and drug resistance of lung cancer. In this study, we investigated the role of miR-497-5p in modulating the function of non-small cell lung cancer (NSCLC). Methods: MiR-497-5p expression in lung cancer tissues and cells was evaluated by qRT-PCR. Cell proliferation was evaluated by CCK-8 assay and colony-formation assay. Cell cycle and cell apoptosis were detected by flow cytometry. The effect of miR-497-5p on the expression of Yes-associated protein 1 (YAP1) and TEA domain family member 1 (TEAD1) was analyzed by qRT-PCR, Western blot and luciferase activity assay. Results: The expression of miR-497-5p was significantly downregulated in lung cancer tissues and cells compared with paired normal tissues and cells. Overexpression of miR-497-5p induced growth retardation and apoptosis of A549 lung cancer cells. Mechanistically, YAP1 and TEAD1 were targeted and downregulated by miR-497-5p. Finally, we found that miR-497-5p increased cisplatin chemosensitivity in A549 cells. Conclusions: MiR-497-5p suppresses cell proliferation and resistance to cisplatin in NSCLC by downregulating the expression of YAP1 and TEAD1.